Exploring The Patterns of Perceived Discrimination among Hindu and Christians Minorities, Regarding Educational Opportunities - Yunus, Asma; Khan, Neha Riaz; Ali, Zaheer (International Journal of Asian Social Science, 2012)
This research was conducted to explore the patterns of perceived discrimination towards religious minorities, mainly in education and social sector. Objectives of the study was to access the difference between Hindus and Christians regarding educational opportunities, to explore the minority’s perception about dealing with the difference in educational opportunities, to analyze the role of curriculum at primary school level regarding minority affairs and to analyze the role of government in hindering the discriminatory practices against religious minorities. In order to collect the data, Snowball sampling technique was used for the study. A sample size of total thirty families comprising of, fifteen Christian and fifteen Hindu were interviewed. Case study research method was used as research technique. It was found that minorities are discriminated and harassed both in education and social sector. They are living in a highly disintegrated state from the majority and are facing identity crises. They poses a lower socioeconomic and literacy status. School curriculum is highly biased and content poses a threat for minorities. Government failed to develop and implement a tolerant and unbiased curriculum and school environment.